Іноземці в Японії у світлі статистики: в'їзд, тимчасове й постійне проживання, натуралізація - Кадзі Ітару (Народна творчість та етнографія, 2009)
Forming history and statistical description of permanent groups of population of Japan is briefly given in the article. The questions of the legislative providing of civil laws of foreigners, principles of naturalization are considered.